EVALUATION OF THE SUPERVISORY ROLE IMPLEMENTATION IN QUALITY IMPROVEMENT AT MIN 4 BIREUEN - Sutisna, Ade Jaya; Yusrianti, Susi (PASCASARJANA UNISNU, 2024)
Madrasah Ibtidaiyah education serves as a good alternative to support public education, especially for students from low-income families. However, improving the quality of Madrasah Ibtidaiyah education remains a problem that needs to be addressed. This research aims to evaluate the implementation of the supervisory role in improving the quality of education at Madrasah Ibtidaiyah Negeri 4 Bireuen. This qualitative case study research employed observations, interviews, and document studies to collect data from the principal, supervisors, and teachers. The results showed that supervision has been carried out regularly, with pre-observation, observation, and evaluation stages. The principal acted as a coordinator, group leader, and evaluator, but his role as a consultant was not well implemented. Evaluation after supervision was conducted to assess the effectiveness of the process and identify areas that required improvement. Supervision plays a crucial role in improving the quality of education by assisting teachers in enhancing their professional and technical abilities. However, the implementation of the supervisory role at MIN 4 Bireuen has not been fully optimal due to obstacles in carrying out the role as a consultant